2018
DOI: 10.1371/journal.pone.0196076
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to hyperbilirubinemia guidelines by midwives, general practitioners, and pediatricians in Indonesia

Abstract: Severe hyperbilirubinemia, which may result in kernicterus, is seen more frequently in low and middle-income countries, such as Indonesia, than in high-income countries. In Indonesia midwives, general practitioners (GPs), and pediatricians are involved in the care of jaundiced newborn infants. It is unknown whether the high incidence of severe hyperbilirubinemia in this country is related to a lack of awareness of existing hyperbilirubinemia guidelines issued by, for example, the World Health Organization, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…We developed a web-based application to make the use of this guideline easier. In a previous study, paediatricians indicated having di culties nding the existing guideline, which hampered their use of it [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We developed a web-based application to make the use of this guideline easier. In a previous study, paediatricians indicated having di culties nding the existing guideline, which hampered their use of it [3].…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the possible diagnosis of kernicterus spectrum disorder (KSD) and consists of a scoring system that includes the highest TSB level, the presence of risk factors, the ndings of neurological examinations performed at rst presentation and at follow-up, the presence of enamel dysplasia, the results of the auditory brainstem response (ABR) test, and MRI ndings [10]. The result is given as one of four categories: de nite kernicterus (10)(11)(12)(13)(14), probable kernicterus (6-9), possible kernicterus (3)(4)(5) and no kernicterus (0-2). This feature might help professionals to prepare for the possible long-term complications of severe hyperbilirubinemia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations